Situational evaluation of brazilian live pharmacy programs - Camargo, Ely Eduardo Saranz; Silva, Jéssica Vaz da; Nunes, Marcos Leandro Alves; Martins, Domingos Tabajara de Oliveira (Seven Editora, 2023)
Many of the Living Pharmacy Programs were implemented before the official launch and agreement on the list of herbal medicines selected by the Ministry of Health (MS) and included in the National List of Essential Medicines (RENAME). The objectives of this study were, through applied forms, to explore the criteria used for the selection of medicinal plants, prescription, follow-up and information to patients. The methodology used was a qualitative and quantitative cross-sectional study carried out through forms applied to the Health Departments of Brazilian municipalities that participated in public notices for financial support, published by SCTIE/MS. Of the 80 forms submitted, approximately 52% were answered. It was found that about 16% of the Programs did not present CFT, that 80 Programs participated in Public Calls of the SCTIE/MS, in the period from month 2012 to month 2021. As for the selection of species, 61% took into account the popular use and 37% the National List of Medicinal Plants of Interest to SUS (RENISUS). According to the dosage scheme, 49% were based on scientific evidence, 20% on popular use and 73% on National Forms of the Brazilian Pharmacopoeia. The prescription of medicinal plants in the Live Pharmacy Programs was carried out in 89% by physicians, 58% by pharmacists and 51% by nurses. Patients who received indications for the use of medicinal plants were around 94%. The Live Pharmacies Programs that are in operation present difficulties, mainly financial, even with the public call notices in the distribution of resources for the creation and maintenance of the Programs, these are still insufficient to meet the local demands. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-133